EKOEFISIENSI DAN FAKTOR PENDUKUNG DALAM IMPLEMENTASINYA PADA PROSES PRODUKSI INDUSTRI KAYU LAPIS DI KALIMANTAN SELATAN - Darni Subari; Udiansyah; Bagyo Yanuwiyadi; Budi Setiawan (Jurnal Penelitian Hasil Hutan, 2012)
This research was objective to determine the implementation ecoefiency and supporting factors, such as perceptions community around industry and financial analysis. The research was conducted inthe plywood industry in South Kalimantan. The results showed that the plywood industry in general bas been applied ecoefiency in the production process. Communities around the plywood industry provide positive support forthe development of the plywood industry. Financial analysis shows that the industry is still profitable with an average of Benefit Cost Ratio(BCR) 1.48.